Xanthophore Distribution of Nemo (Amphiprion ocellaris) Skin Based on various Concentrations of Carotenoid Sources - Pratiwi, Rini; Karim, Muhammad Yusri; Trijuno, Dody Dh (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Abstract The decreased color intensity of Nemo is related to the amount of carotenoid concentration in the xanthophore of Nemo's skin. Therefore, efforts are needed to maintain stable carotenoid production. Tomato is one of the most abundant carotenoid producers. The utilization of carotenoids can maintain the morphological color of aquatic organisms. This study aimed to analyze the effect of carotenoid compounds on total carotenoid content, the size, and distribution of xanthophores on Nemo skin. A total of 60 Nemo with an average initial weight of 0.84±0.14 g and an average length of 2.95±0.08 cm. The research was conducted using a completely randomized design (CRD), consisting of four carotenoid concentrations in addition to fish pellet, 0%, 0.5%, 1%, and 1.5% with three replications. The results showed that the optimum dose of carotenoid compounds in increasing the total carotenoid content in nemo fish skin is 1.5%. Carotenoids added to the fish feed affected the distribution and maturity of xanthophore. However, it did not affect the size of the xanthophore. Highlight Research Nemo contains three types of pigment cells, namely melanophores, xanthophores, and iridophores. Carotenoid supplementation is related to xanthophore in fish skin The pigment pattern is determined mainly by the number, size, and distribution of different cell types xanthophores were not found in the histology HE (hematoxylin-eosin) staining method in fish skin.